CHARACTERIZATION OF ENVELOPE E PROTEIN OF DENGUE VIRUS INDNESIA ISOLATE - Rantam F A; Soetjipto Soetjipto; Dachlan Y P (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
Dengue virus is a human pathogen that has as an increasingly important public health threat. These virus have four serotypes (DEN-1, DEN-2, DEN-3, DEN-4). There is no specific treatment for any pathogenic dengue virus and there are few vaccines available. This study was carry out to E protein characterization from dengue virus infected C5/36 cells for vaccine candidate. We found that E protein induced antibody response. The data of the reactivity on the nitrocellulose membrane between E protein against polyclonal and monoclonal antibodies on western blot analysis, shown that the E protein whisc was once of dengue virus protein has immunogenic. The Indonesia isolate had no difference with the Phillipine isolate. The result suggested that all of the E protein dengue virus strain have peptides overlapping. Also promising for he production of immunogenic particulate proteins, especially DEN protein for the four strains.